Higher order affordances for reaching: Perception and performance. Issue 5 (May 2019) - Wagman, Jeffrey B; Cialdella, Vincent T; Stoffregen, Thomas A
Affordances are available behaviours emerging from relations between properties of animals and their environment. In any situation, multiple behaviours are available, that is, multiple affordances exist. We asked whether participants could detect means–ends relations among affordances (i.e., higher order affordances) in the context of reaching to a maximum height. We both assessed perceived affordances and evaluated actual reaching ability. In Experiment 1, we co-varied higher order goals (reaching to touch vs reaching to grasp) and the lower order effectors used to achieve the goals (fingertips vs a hand-held tool). In Experiment 2, we varied the lower order posture from which reaching would occur (standing vs kneeling). In both experiments, perceived maximum reaching height reflected relations between lower order means (effectors and postures) and higher order ends (reaching goals), and judgments closely reflected actual performance. We conclude that participants demonstrated prospective sensitivity to higher order affordances for reaching extended across multiple levels of the means–ends hierarchy.